2020
DOI: 10.3390/jcm9124053
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain and Non-Classroom Teaching in Times of the COVID-19 Pandemic: Analysis of the Impact on Students from Two Spanish Universities

Abstract: The lockdown, due to the coronavirus, has led to a change in lifestyle and physical activity in Spanish university students. The objective of this study was to analyze the prevalence of musculoskeletal pain and changes in physical activity and self-perceived stress in the student bodies of two Spanish Universities during the lockdown. A cross-sectional study was carried out in a sample of 1198 students (70.6% women). The main instruments used for measuring were the Standardized Kuorinka Modified Nordic Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 48 publications
(32 reference statements)
4
32
1
10
Order By: Relevance
“…Our results contradict those of Majumdar et al [2] and Leirós-Rodríguez et al [38], in which the pandemic did not have an adverse effect on NP in students. The results of other studies [5,39] were correlated with ours in terms of the adverse effect of the pandemic on NP among college students.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results contradict those of Majumdar et al [2] and Leirós-Rodríguez et al [38], in which the pandemic did not have an adverse effect on NP in students. The results of other studies [5,39] were correlated with ours in terms of the adverse effect of the pandemic on NP among college students.…”
Section: Discussioncontrasting
confidence: 99%
“…The frequency and duration of this pain varied among participants, but there was a statistical signi cant in the pain duration range of 1-6 hours per day compared to other groups. Previous studies also showed that during e-learning the student tend to adopt inappropriate postures that can cause pain and musculoskeletal alterations, especially in the upper limbs and spine (19).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is also interesting for gymnasts to try to understand if and how lifestyles, especially in professional athletes, affect the onset of musculoskeletal pain. This is all the more interesting in a historical period such as the present one, in which the restrictions on the usual sporting activity imposed by the COVID-19 pandemic have led to inevitable postural and musculoskeletal dysfunctions [20,21].…”
Section: Introductionmentioning
confidence: 92%